Remittances and Household Expenditure Behaviour in Senegal - Teresa Randazzo; Matloob Piracha (Institute for the Study of Labor (IZA), 2014)
This paper analyses the impact of remittances on household expenditure behaviour in Senegal. We use propensity score matching and OLS methods to assess the average impact of remittances on several household budget shares. Our results show a productive use of international remittances in Senegal. However, the impact of remittances disappears when the marginal spending behaviour is considered, i.e., households do not show a different consumption pattern with respect to their remittance status. Therefore, in the decision on how to allocate expenditure, remittances are treated just as any other source of income.
Keywords: F24; O12; O15; 330; remittances; household expenditure; Senegal